Shippen family papers - Livingston, Anne Home Shippen, 1763-1841.; Shippen, Edward, 1826-1911.; Shippen, Thomas Lee, 1765-1798.; Shippen, William, 1712-1801.
Correspondence, diaries, account books, memorandum books, legal and business records, indentures, and other papers of Anne Home Shippen Livingston, Edward Shippen, Thomas Lee Shippen, William Shippen, and other family members. Also includes papers of the Nicholson family. Correspondents include Thomas Jefferson, Francis Scott Key, Arthur Lee, Richard Henry Lee, James Madison, and George Washington.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Members of the Shippen family of Philadelphia, Pa.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Jefferson, Thomas, -- 1743-1826 -- Correspondence; Key, Francis Scott, -- 1779-1843 -- Correspondence; Lee, Arthur, -- 1740-1792 -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Nichols family; Shippen family; Pennsylvania -- History; Pennsylvania -- Social life and customs; Philadelphia (Pa.) -- History; Philadelphia (Pa.) -- Social life and customs